Successful transition towards a virtuous cycle of human development and economic growth : country studies - Gustav Ranis; Frances Stewart (Yale University, Economic Growth Center, 2007)
This paper explores the two-way links between Economic Growth and Human Development by examining the performance of some countries which have been successful in both dimensions and a few which have not. The specific aim is to examine the historical experience of six countries in order to determine how a system can move to a situation in which improvements in Human Development accompany and support higher rates of growth which, in turn, contribute to further improvements in Human Development as the basic societal objective.
Keywords: O11; O15; O57; 330; Economic growth; human development; comparative country studies